Normative profile of the efficacy and way of execution for the block in women's volleyball from under-14 to elite levels - Echeverria, C.; Ortega, E.; Palao, J. M. (Montenegrin Journal of Sports Science and Medicine, 2020)
This study aimed to establish reference values for technical performance profile of the block regarding execution and efficacy according to the category of competition in female volleyball. The sample of the study was composed of a total of 9,024 blocks from 187 sets of 48 matches played by the top eight teams of under-14, under-16, under-18, 2nd national senior division, 1st national senior division, and international senior division. The design of the study was observational. The study`s variables were the category of competition, game phase, block performance, block zone, number of player blocking, block intervention, and attack tempo. A descriptive and inferential analysis of official matches in all the levels of competition was carried out. The results show that at higher levels of competition, there was an increase in the number of errors, the number of direct points, and the number of contacts that limit the counterattack of the opponent. At higher levels, there is also higher participation of players in the block, mainly against 3rd tempo attacks. These values can help to monitor the evolution of female volleyball players and to establish training and competition goals.